Association of phenotypic age and accelerated aging with severity and disability in patients with acute ischemic stroke - Liu, Yongkang; Wang, Jiangchuan; Wei, Zicheng; Wang, Yu; Wu, Minghua; Wang, Jianhua; Chen, Xiao; Chen, Rong (The Journal of nutrition, health & aging, 2024)
Biological age may be more accurate than chronological age in determining chronic health outcomes. However, few studies have shown the association between biological age and acute ischemic stroke (AIS). In this study we showed the association between phenotypic age (PhenoAge) or accelerated aging and severity and disability in patients with AIS. Retrospective study. 936 patients with AIS during January 2019 to July 2021 and 512 patients during June 2022 to July 2023 for a validation. Stroke severity was evaluated based on the National Institute of Health stroke scale (NIHSS) questionnaire scale. Disability was evaluated by modified Rankin Scale. PhenoAge was calculated based on chronological age and 9 clinical chemistry biomarkers. Logistic regression analyses were applied to estimate the relationship between PhenoAge and the severity and disability. PhenoAge (odds ratio [OR] = 1.03, 95% confidence interval [CI]: 1.0–1.04, for NIHSS ≥ 5; OR = 1.05, 95%CI: 1.03−1.07, for NIHSS ≥ 10) was independently associated with stroke severity. The probability of NIHSS ≥ 5 or NIHSS ≥ 10 was significantly increased in individuals with accelerated ageing versus individuals with no accelerated aging (age gap: OR = 1.79, 95%CI: 1.18−2.72; OR = 3.53, 95%CI: 1.60−7.77; phenotypically older vs. phenotypically younger: OR = 2.01, 95%CI: 1.21−3.35; OR = 3.69, 95%CI: 1.36−10.0). Similar trends was observed when accelerated aging was defined by residual discrepancies between PhenoAge and chronological age (OR = 1.02, 95%CI: 1.01−1.04, for NIHSS ≥ 5; OR = 1.05, 95%CI: 1.02−1.08, for NIHSS ≥ 10). The area under the curve of PhenoAge was higher than that of chronological age in identifying patients with NIHSS ≥ 5 (0.66, 95%CI:0.62−0.70 vs. 0.61, 95%CI: 0.58−0.65, p < 0.01) and NIHSS ≥ 10 (0.69, 95%CI:0.60−0.77 vs. 0.63, 95%CI: 0.55−0.72, p = 0.05). The probability of severe disability was significantly increased in individuals with accelerated aging versus individuals with no accelerated aging (age gap: OR = 2.87, 95%CI: 1.09−7.53; phenotypically older vs. phenotypically younger: 4.88 (1.20−19.88). Similar results were observed in the validation population. PhenoAge or accelerated aging is associated with stroke severity and disability even after adjusting for chronological age.